2003
DOI: 10.1128/jvi.77.20.10799-10807.2003
|View full text |Cite|
|
Sign up to set email alerts
|

Aichi Virus Leader Protein Is Involved in Viral RNA Replication and Encapsidation

Abstract: Aichi virus, which is associated with human acute gastroenteritis (41), is a member of the genus Kobuvirus of the family Picornaviridae (31, 42). This virus was first isolated in 1989 from a stool specimen from a patient with oyster-associated nonbacterial gastroenteritis in Aichi, Japan (41), and the complete genome sequence was determined in 1998 (42). The single-stranded, positive-sense RNA genome of Aichi virus consists of 8,280 nucleotides (nt) and a poly(A) tract and encodes a polyprotein of 2,432 amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…The newly synthesized progeny RNA is encapsidated into the capsid proteins as soon as RNA is syn- thesized. In the case of Aichi virus, which belongs to the genus Kobuvirus of the family Picornaviridae, L is involved in viral RNA replication and encapsidation, since the accumulation of empty capsids was observed in the case of an L-deleted mutant virus (31). In this study, the peaks of empty capsids are almost similar among all the viruses.…”
Section: Discussionsupporting
confidence: 53%
“…The newly synthesized progeny RNA is encapsidated into the capsid proteins as soon as RNA is syn- thesized. In the case of Aichi virus, which belongs to the genus Kobuvirus of the family Picornaviridae, L is involved in viral RNA replication and encapsidation, since the accumulation of empty capsids was observed in the case of an L-deleted mutant virus (31). In this study, the peaks of empty capsids are almost similar among all the viruses.…”
Section: Discussionsupporting
confidence: 53%
“…In fact, numerous attempts to identify an RNA encapsidation signal have failed. A single study reports that the encapsidation signal could lie within the 5′UTR of the Aichi virus together with the L protein 71 , 72 . However, a recent paper, which tends to favor the second model of encapsidation, also proposes a mechanism by which the triple interaction vRNA-2C-VP3 would be sufficient to explain the specificity of picornavirus encapsidation 73 .…”
Section: Viral Cyclementioning
confidence: 99%
“…Aichi virus L and 2A functions remain unknown 3. L protein has no autocatalytic activity and is not involved in polyprotein cleavage, but is probably involved in both viral RNA replication and encapsidation 11. It was also reported that the 2A proteins of kobuviruses, as well as human parechoviruses and avian encephalomyelitis virus, have conserved motifs (H‐box/NC and transmembrane domain) that are characteristic of a family of cellular proteins (H‐rev107) involved in the control of cell proliferation 12 and in viral RNA replication 13.…”
Section: Genetic Structure and Function Of Kobuvirusesmentioning
confidence: 99%